The Effect of Motivation and Compensation as Well as Leadership Style on the Performance of Employees of the Population and Civil Registration Office of Samarinda City with Job Satisfaction as an Intervening Variable - Sanusi, Otoh; Soeginto K, Eddy; Yudhyani, Eka (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: The Effect Of Motivation And Compensation As Well As Leadership Style On The Performance Of Employees Of The Population And Civil Registration Office Of Samarinda City With Job Satisfaction As An Intervening Variable Design/methodology/approach: using a quantitative approach. In this study, the data used are primary data and secondary data. Sampling in this study uses the census method or also called total sampling. Taking a total sampling due to the population being less than 100. In other words, all existing population members will be part of the research sample, while the number of samples for this research is 93 employees of the Samarinda City Population and Civil Registration Office. Findings: The results of this study showed that motivation (X1) had a positive and significant effect on performance (Y), compensation (X2) had a positive and significant effect on performance (Y), leadership style (X3) had no positive and significant effect on performance (Y), motivation (X1) had a positive and significant effect on job satisfaction (Z), compensation (X2) had a positive and significant effect on job satisfaction (Z), leadership style (X3) had a positive and significant effect on satisfaction work (Z), job satisfaction (Z), has a positive and significant effect on performance (Y), motivation (X1) has a positive and significant effect on performance (Y) through job satisfaction (Z) as an intervening variable, compensation has a positive and significant effect on performance (Y) through job satisfaction (Z) as an intervening variable, leadership style has a positive and significant effect on performance (Y) through job satisfaction (Z) as an intervening variable of the Population and Civil Registration Office Samarinda City.